Influence of Teachers’ Improvisation of Heat Producing Materials on Acquisition of Science Skills among Pre-primary School Learners in Kiambu, Kenya - Githui, Millicent Wandia; Koech, Peter Kibet; Thinguri, Ruth (Journal of Education, Society and Behavioural Science, 2021)
Acquisition of science skills among pre-primary school learners has had its fair share of challenges with many pre-primary school learners manifesting low competencies in manipulation, experimentation and observation skills. The purpose of this study was to assess the influence of teachers’ improvisation of heat-producing materials on acquisition of science skills among preprimary school learners. The study was guided by Social Constructivism and Instructional Theories. The study adopted mixed methodology and applied concurrent triangulation research design. Qualitative data were analyzed thematically along the objectives and presented in narrative forms. Quantitative data were analyzed descriptively and inferentially using linear regression analysis with the help of Statistical Packages for Social Science (SPSS 23) and presented using tables. These results indicate that there is significant relationship between teachers’ improvisation of heatproducing materials and acquisition of science skills among pre-primary school learners (p=0.000< 0.05). The study established that pre-primary school learners’ manifest low science skills. That is, their manipulation, experimentation and observation skills are still below average. The study recommends that the pre-primary curriculum developers emphasize the improvisation of heat producing materials as much as possible and frequent inspections are carried out. For future studies, researchers may put greater interest in conducting a similar study with national scope to certain the influence of improvised instructional materials on the levels of science skills among preprimary learners.
Keywords: Pre-primary; science skills; teaching; practical knowledge